Molecular characterization of eight horse breeds in Algeria using microsatellite markers - MOHAMMED EL AMINE BENHAMADI; NAIMA BERBER; MOHAMMED BENYAROU; ABDELKADER AMEUR AMEUR; HADI YOUSSOUF HADDAM; MOHAMMED PIRO; SEMIR BECHIR SUHEIL GAOUAR (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Amine BME, Naima B, Mohammed B, Abdelkader AA, Youssouf HH, Mohammed P, Suheill GSB. 2020. Molecular characterization of eight horse breeds in Algeria using microsatellite markers.  Biodiversitas 21: 4107-4115. The Algerian horse population Bar, Origin Barb unknown, Arabian-Barb, Arabian, Thoroughbred (Pur sang); French Trotter, Algerian saddle, and Saddle are under a significant loss of genetic variability. This should be evaluated before any breed conservation and management program. For this purpose, genetic analyzes of diversity and differentiation were carried out on eight breeds horses reared in Algeria with 17 microsatellites. All microsatellite markers were highly polymorphic in all Breeds. A total of 170 alleles from 17 microsatellite loci were detected in 279 horses. The average number of alleles per locus was highest in Arabian-Barb horses (7.88) and lowest in Saddle breed (4.94). The observed heterozygosity interbreeds ranged from 0.685 to 0.625 for Barb and Saddle, while the expected heterozygosity was ranged from 0.746 to 0.678 for Arabian-Barb and Algerian Saddle respectively, the Ho value is lower than that of  He value. Genetic diversity between breeds was significant, based on Fst. Three different approaches to assess genetic relationships have been applied; namely, genetic distances, factorial correspondence analysis, and admixture analysis have shown that a significant amount of genetic variation is maintained in populations of native horses and other breeds: the Barb, Arabian-Barb, Barb (Oi). Algerian Saddle and Saddle breeds appear to be the most genetically related and support that there are crosses between these two breeds.